Architecture and characterization of the P4DI CMOS hybrid pixel sensor. (26th September 2017) - Chatzistratis, D.; Theodoratos, G.; Kazas, I.; Zervakis, E.; Loukas, D.; Lambropoulos, C.P.
Abstract: Gamma ray imaging can be used for the extraction either of the activity map of a source or of the attenuation map of an object or both, as well as for the identification of the material composition of the emitting source or the object. All these imaging modalities can benefit from instruments giving the information of the energy of the converted photons and also the spatial and time coordinates of the conversion. The P4DI CMOS and hybrid provides the core technology for this task being a 2-D array based on Cd(Zn)Te material for the sensing layer. It consists of 1250 pixels with 400 μ  m pitch. The energy resolution of the 241 Am photopeak is 3.5 keV, time resolution is less than 12 μ  s and power consumption is less than 100 mW. Architecture and characterization are described.